Action of mineralocorticoid and sex steroids on sodium transport in toad skin - Cirne, Bario; Malnic, Gerhard (Elsevier, 1972)
Short circuit current (s.c.c.) and potential difference (PD) were measured in control toad skin and after the addition of aldosterone and deoxycorticosterone acetate. A significant effect was seen only when skins were preincubated for 12 h with the hormones. After this preincubation with mineralocorticoids or with sex steroids (estradiol, progesterone and testosterone), a kinetic study was performed measuring s.c.c. at different levels of Na+ in the external medium. The results indicated that Na+ transport followed Michaelis-Menten kinetics between 5 and 50 mequiv/l Na+. V was significantly higher in all hormone-preincubated skins, the effect of mineralocorticoids being considerably greater than that of sex steroids. On the other hand, Km was not significantly different from controls in most cases, and did not show a definite trend in the remainder, indicating no major alteration in the affinity between Na+ and its transport system. Skin resistances fell in both chloride and sulfate Ringer solutions with mineralocorticoids, but only in the latter medium with estradiol and progesterone, and not at all with testosterone. In conclusion, sex steroids stimulate Na+ transport significantly, but to a lesser degree than mineralocorticoids; their effect on skin conductance is relatively smaller than that on Na+ transport. © 1972.